Clinical value of long noncoding RNA ZEB1 anti-sense1 in cancer patients: A meta-analysis. Issue 31 (31st July 2020) - Cheng, Sixiang; Guo, Shengyu; He, Hairong; Kaminga, Atipatsa Chiwanda; Xu, Huilan
Abstract: Background: The high expression of long noncoding RNA ZEB1 anti-sense1 (ZEB1-AS1) has been reported in several types of cancer. However, most studies investigating this phenomenon were either case reports or used small patient samples. The objective of this meta-analysis was to clarify the potential clinical values of ZEB1-AS1 in various cancers. Materials and methods: The PubMed-MEDLINE, Web of Science, and EMBASE databases were searched, using systematic search terms, to find relevant research reports on this subject. The combined hazards ratios (HRs) and corresponding 95% confidence intervals (CIs) were calculated to explore the association between ZEB1-AS1 expression and overall survival (OS). The combined odd ratios (ORs) were calculated to evaluate the association between ZEB1-AS1 expression and pathological parameters. Data analysis was conducted in R software version 3.4.2. and Stata version 12.0 (College Station, TX: Stata Corp LP). Results: Ten studies including 963 cancer patients were selected as suitable for this study. The pooled hazards ratio (HR) indicated that high ZEB1-AS1 expression was strongly associated with poor OS (pooled HR = 2.26, 95% CI: 1.80–2.85, P < .0001) in the Chinese cancer patients. Also, a high expression of ZEB1-AS1 was related to metastasis (pooled HR = 3.38, 95% CI: 1.91–6.00, P < .0001), and advanced tumor stage (pooled HR = 0.48, 95% CI: 0.29–0.81, P = .005). The up-regulation of ZEB1-AS1 was not significantly associated with histological differentiation ( P = .39), sex ( P = .001), and age ( P = .372) of cancer patients. Conclusion: The high expression of ZEB1-AS1 significantly predicted poor OS, poor metastasis, and high tumor stage in cancer patients, demonstrating that high ZEB1-AS1 expression may serve as a biomarker of poor prognosis in the Chinese cancer patients. Abstract : Supplemental Digital Content is available in the text